Novel Antimicrobial Treatment Strategy Based on Drug Delivery Systems for Acute Otitis Media - Kono, Masamitsu; Umar, Nafisa K.; Takeda, Saori; Ohtani, Makiko; Murakami, Daichi; Sakatani, Hideki; Kaneko, Fumie; Nanushaj, Denisa; Hotomi, Muneki (Frontiers in Pharmacology, 2021)
Despite tremendous success of pneumococcal conjugated vaccine and antimicrobial treatment by amoxicillin, acute otitis media (AOM) still remains as a great medical concern. Failure of antimicrobial treatment includes several factors. The middle ear cavity is surrounded by bone tissue, which makes it difficult to maintain sufficient concentration of antibiotics. Tympanic membrane of AOM patients thickens and actually becomes a barrier for topical therapy. This review discusses novel antimicrobial treatment strategies based on drug delivery systems (DDS) for AOM. To deliver drugs enough to kill the pathogenic bacteria without systemic side effects, the development of new antimicrobial treatment strategy applying innovative drug DDS has been expected. The sustained-release DDS can achieve sufficient time for antimicrobial concentrations to exceed minimum inhibitory concentration (MIC) for time-dependent antibiotics as well as enough maximum concentration for dose-dependent antibiotics to eradicate causative pathogens in the middle ear. The development of trans-tympanic membranes of DDS, such as hydrogels with chemical permeation enhancers (CPEs), is another attractive strategy. Phage is a promising strategy for developing DDS-based therapies. The DDS formulations enable antimicrobial treatment of AOM by a single dose and thus, an attractive future antimicrobial treatment for AOM.